Distribution and population structure of endobacteria in arbuscular mycorrhizal fungi at North Atlantic dunes. Issue 12 (December 2018) - Lastovetsky, Olga; Ahn, Ezekiel; Mondo, Stephen; Toomer, Kevin; Zhang, Aolin; Johnson, Lynn; Pawlowska, Teresa
Abstract Arbuscular mycorrhizal fungi (AMF, Glomeromycotina), in addition to forming symbioses with the majority of land plants, harbor vertically transmitted endosymbiotic bacteria 'Candidatus Glomeribacter gigasporarum' (Ca Gg) and 'Candidatus Moeniiplasma glomeromycotorum' (Ca Mg).Ca Gg is a nonessential mutualist of AMF, whereas the lifestyle ofCa Mg is unknown. To start unraveling the interactions between AMF and their endosymbionts in nature, we examined diversity and distribution of AMF-associated endobacteria in North Atlantic dunes at Cape Cod. Of nearly 500 foredune AMF isolates successfully genotyped during a systematic study, 94% were classified as Gigasporaceae. Two percent of all AMF spores harboredCa Gg, and 88% containedCa Mg.Ca Gg was found only in the Gigasporaceae, whereasCa Mg was present in Gigasporaceae, Acaulosporaceae, and Diversisporaceae. Incidence ofCa Gg across AMF was not affected by any of the environmental parameters measured, whereas distribution ofCa Mg in one of the fungal hosts was impacted by plant density.Ca Mg populations associated with AMF individuals displayed high levels of genetic diversity but no evidence of gene flow, suggesting that host physical proximity is not sufficient to facilitate horizontal transmission ofCa Mg. Finally, in addition to a novel lineage ofCa Gg, we discovered that AMF likely harborBurkholderia -related bacteria with close phylogenetic affinity to free-livingBurkholderia and endobacteria of other Mucoromycota fungi.